Neanderthal Paintings? Production of Prototypical Human (Homo Sapiens) Faces Shows Systematic Distortions. (January 2014) - Carbon, Claus-Christian; Wirth, Benedikt Emanuel
People's sketches of human faces seem to be systematically distorted: The eye position is always higher than in reality. This bias was experimentally analyzed by a series of experiments varying drawing conditions. Participants either drew prototypical faces from memory (studies 1 and 2: free reconstruction; study 3: cued reconstruction) or directly copied average faces (study 4). Participants consistently showed this positioning bias, which is even in accord with facial depictions published in influential research articles by famous face researchers (study 5). We discuss plausible explanations for this reliable and stable bias, which is coincidentally similar to the morphology of Neanderthals.